The Determinants of the Foreign Direct Investment on the Macroeconomic Variables: The Case of the Algerian Economy - Smahi, Ahmed (American Finance & Banking Review, 2018)
Foreign direct investment in Algeria as a percentage of GDP represented 0.9% during the last decade. The goal of this study is to assess the effect of Foreign Direct Investment on Algerian economy through an empirical analysis by applying the bounds testing ARDL and ECM-ARDL using annual data for the period 1970-2014. As far as the role of FDI is concerned, we shall try to highlight its effect that may show causal relationships to non-hydrocarbon GDP, non-hydrocarbon export, industry and employment in long run. Our estimation of an ARDL model indicates that the political and macroeconomic stability are not enough to attract FDI to help non-hydrocarbon sectors drive economic growth.